A low-cost PC-based range finder system - Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn (International Association of Computer Science and Information Technology Press, 2013)
Now computerization is the most popular, reliable and flexible design for various types of control and communication systems. Sound navigation and ranging (SONAR) is a modern ultrasonic range finding technique used for collecting the information about a distant object without any physical contact. In this research work a PC based active SONAR system is proposed. A pair of 40 kHz piezoelectric ultrasonic transducers is used in this project. A driver-software named is developed using turbo C language aimed at IBM PC and its clone machines. The software provides necessary support for interfacing the hardware as well as calculations. A numbers of test were done and found that the proposed system performances are good in terms of accuracy ±5%, simplicity,cost and power consumption.